Comparative Analysis of the Intellectual Property Rights of Three Former British Colonies of the Sub-Continent- Bangladesh, India, and Pakistan - Abbas, Muhammad Haris (Law and Policy Review, 2024)
The study examined the intellectual property rights, judicial effectiveness, and freedom of investment in the three British colonies of Asia-Pakistan, India, and Bangladesh. The aim of the study was to assess the progress these countries have made in protecting intellectual property rights, enhancing judicial effectiveness, and promoting freedom of investment. For this purpose, the researcher collected data from two international platforms: the International Property Right Alliance and the Economic Index of The Heritage Foundation, covering the last ten years excluding 2024, due to the unavailability of data for that year. Researcher comparatively analyzed the data from 2014-2023 on the protection of intellectual property rights, judicial effectiveness, and freedom of investment. Based on the analysis, the researchers concluded that the protection of intellectual rights is strongest in India, followed by Pakistan, and then Bangladesh. Using a seven-point Likert scale, India was found to be at the middle level of protection, Pakistan at middle to low level and Bangladesh at the lowest level of protecting intellectual rights. However, there is a negative significant relationship found between the protection of intellectual property rights and judicial effectiveness, but there is a positive significant relationship between freedom of investment and protection of intellectual rights.